Can We Use SE-specific Sentiment Analysis Tools in a Cross-Platform Setting? - Novielli, Nicole; Calefato, Fabio; Dongiovanni, Davide; Girardi, Daniela; Lanubile, Filippo (2020 IEEE/ACM 17th International Conference on Mining Software Repositories (MSR), 2020)
In this paper, we address the problem of using sentiment analysis tools 'off-the-shelf', that is when a gold standard is not available for retraining. We evaluate the performance of four SE-specific tools in a cross-platform setting, i.e., on a test set collected from data sources different from the one used for training. We find that (i) the lexicon-based tools outperform the supervised approaches retrained in a cross-platform setting and (ii) retraining can be beneficial in within-platform settings in the presence of robust gold standard datasets, even using a minimal training set. Based on our empirical findings, we derive guidelines for reliable use of sentiment analysis tools in software engineering.